2014
DOI: 10.3329/bjar.v39i1.20143
|View full text |Cite
|
Sign up to set email alerts
|

Performance of different protocols on in vitro tuberization in potato (Solanum tuberosum)

Abstract: Five protocols of micro tuberization were used to induce large size microtuber in three recommended potato varieties, namely Cardinal, Diamant, and Heera under complete dark condition. Tuberization was the earliest (11.8 days) in the protocol P 2 (MS + 5 mg/l BAP + 500 mg/l CCC + 8% sucrose), which was closely followed by that in P 1 (12.7 days) (MS + 5 mg/l BAP + 50 mg/l coumarin + 8% sucrose) . Maximum number of microtubers/flask (12.8) was obtained from the protocol P 1 followed by that of P 2 (11.6) that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Protacio and Flores (1992); reported that the free polyamines in explants increased the microtuberization in high and low percentage of sucrose concentrations. Zakaria et al (2014); observed that the highest percentage (52.2%) of >300 mg size and lowest percentage (19.3%) of <150 mg size microtuber was produced in 30 days old plantlet with MS media containing 40 mg.l -1 K + 10 mg.l -1 BA + 9% sucrose in the variety Diamant. Dhital and Lim (2012); reported that 1/2 MS liquid medium containing 8% sucrose and 1.22 gl -1 KNO3, 1.41 gl -1 NH4H2PO4,; 0.23 gl -1 Ca(NO3)24H2O,; and 0.74 gl -1 MgSO4 produced the highest percentage (50%) of medium to large-sized (>500 mg) microtubers.…”
Section: Percentage Of Microtuberizationmentioning
confidence: 96%
See 2 more Smart Citations
“…Protacio and Flores (1992); reported that the free polyamines in explants increased the microtuberization in high and low percentage of sucrose concentrations. Zakaria et al (2014); observed that the highest percentage (52.2%) of >300 mg size and lowest percentage (19.3%) of <150 mg size microtuber was produced in 30 days old plantlet with MS media containing 40 mg.l -1 K + 10 mg.l -1 BA + 9% sucrose in the variety Diamant. Dhital and Lim (2012); reported that 1/2 MS liquid medium containing 8% sucrose and 1.22 gl -1 KNO3, 1.41 gl -1 NH4H2PO4,; 0.23 gl -1 Ca(NO3)24H2O,; and 0.74 gl -1 MgSO4 produced the highest percentage (50%) of medium to large-sized (>500 mg) microtubers.…”
Section: Percentage Of Microtuberizationmentioning
confidence: 96%
“…A relatively higher number of microtubers observed in treatments with sucrose concentration 3% and 8% while in the control treatment (0%) no microtubers were formed (Wazir et al, 2015). Maximum number of microtubers (12.8) was obtained in MS medium containing 5 mg.l -1 BAP, 50 mg.l -1 coumarin and 8% sucrose that followed by MS medium including 5 mg.l -1 BAP, 500 mg.l -1 CCC and 8% sucrose that contained growth retardant (Zakaria et al, 2014). Gami et al (2013); explained that for microtuber production, high level of sucrose (8%) gave promising results than low level of sucrose (3%).…”
Section: Number Of Microtubersmentioning
confidence: 98%
See 1 more Smart Citation